Nutritional profile of the morbidly obese patients attending a bariatric clinic in a South Indian tertiary care centre - Mini Joseph; Nitin Kapoor; Shobana Ramasamy; Stephen Amarjeet Jiwanmall; Dheeraj Kattula; Vijay Abraham; Inian Samarasam; Thomas Paul; Nihal Thomas (Ожирение и метаболизм, 2017)
Background: Obesity is sweeping across continents and is a major public health concern of the modern society. Aims: The main objective of this study was to study the demographic, anthropometric and dietary patterns of the morbidly obese and study region wise variation in their nutrient intake. Materials and Methods: The study was conducted on 101 morbidly obese individuals from different regions of India who attended the Bariatric clinic of a tertiary care hospital in India. Their socio-demographic details, anthropometric measurements were collected. The dietary assessment was done using a 24 hour dietary recall and a food frequency questionnaire. The study was approved by the Institutional review board and informed consent was obtained from them. Results: More than 3/4th of the patients were females and 61 per cent had Type 2 diabetes mellitus. The mean age of the male and female population was 41.3 + 15.5 years and 36.7 + 11.9 years respectively. Their mean BMI was 41kg/m2. The mean daily intake of calories was more than 2200kcal/day with a gross deficit in the intake of micronutrients. Bonferroni Test showed that there was region wise variation in dietary intake, South Indian female population had the lowest intake of the micronutrients and those from East India had the highest intake. In the male population, there was a significant regional difference in intake of Proteins (p=0.039) and Energy (p=0.024). Independent Sample T test showed that South Indian had the highest intake of Energy and proteins. Anthropometric measures showed positive relation with various macronutrient intakes. Conclusion: The obese patients require intense counselling by a dedicated team of an endocrinologist, psychiatrist, dietician, bariatric surgeon and a social worker to make achievable changes in the quality of life of the morbidly obese patients. Regional influences must be considered when counselling the patient.